2021
DOI: 10.14414/jbb.v10i2.2272
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job satisfaction, workplace spirituality and organizational commitment on work productivity with organizational citizenship behavior (OCB) as intervening variable (Case study on Bank Muamalat Indonesia KC Solo)

Abstract: The study aims to identify and analyze the influence of job satisfaction, organizational commitment, workplace spirituality on work productivity with Organizational Citizenship Behavior (OCB) as an intervening variable. The population of this study consists of all employees of Muamalat Bank Solo Branch. The data were collected by a questionnaire distributed to 40 employees of Muamalat Bank Solo Branch. This study uses a saturated sample technique or total sampling. The data were analyzed using multiple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the early stages of this research, a hypothesis was formulated about the effect of job satisfaction on organizational citizenship behavior which was positive. In accordance with research conducted by Ridlo, et. al.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship...supporting
confidence: 92%
“…In the early stages of this research, a hypothesis was formulated about the effect of job satisfaction on organizational citizenship behavior which was positive. In accordance with research conducted by Ridlo, et. al.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship...supporting
confidence: 92%
“…As stated by Ridlo et al (2021), employee satisfaction holds paramount significance among several factors influencing the effectiveness of an organization. Key indicators of job satisfaction encompass (1) satisfaction with work, (2) satisfaction with salary, (3) satisfaction with promotion, (4) satisfaction with superiors, and ( 5) satisfaction with colleagues.…”
Section: Definition Of Job Satisfactionmentioning
confidence: 99%
“…In this context, OCB can act as a mediator or liaison between the independent and dependent variables in a study. The following studies on the role of OCB as a mediator include the one from Ridlo et al (2021), which found that OCB acts as an intervening variable and that job satisfaction, workplace spirituality, and organizational commitment all positively and significantly affect employee work performance. Hastuti and Wulandari (2022) showed that the mediating variable OCB was able to mediate the positive and significant relationship between Workplace Fun and performance.…”
Section: Mediation Role Of Ocbmentioning
confidence: 99%